2005
DOI: 10.1111/j.1365-2929.2005.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Misunderstandings: a qualitative study of primary care consultations in multilingual settings, and educational implications

Abstract: It is routine for GPs in inner London practices to manage consultations with patients with culturally different communicative styles from their own. Specific training in identifying these problems and preventing/repairing them in the consultation is essential. This level of awareness-raising is more crucial than general discussions of culturally different health belief models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 17 publications
1
75
0
Order By: Relevance
“…This is particularly important to bear in mind as interaction must be conducted in a specifi c language, and participants in an interethnic encounter oftentimes have unequal profi ciency levels. Numerous studies have shown that misunderstandings predominantly result from limited profi ciency in one or more of the languages of the participants in the interethnic encounter, especially the dominant language, including limited awareness of different contextualization cues (e.g., Bremer et al 1996 ;Birkner and Kern 2000 ;Roberts 2000 ;Roberts et al 2005 ). Roberts et al ( 2005 : 473), for instance, found in a study of 232 general practice consultations in four inner -London medical practices that lack of profi ciency in the languages involved in the encounters was the main problem in medical encounters in this multilingual community: " Twenty per cent of all the consultations we fi lmed contained misunderstandings caused by language/cultural differences, where talk itself is the problem.…”
Section: Language In " Intercultural Communication "mentioning
confidence: 99%
“…This is particularly important to bear in mind as interaction must be conducted in a specifi c language, and participants in an interethnic encounter oftentimes have unequal profi ciency levels. Numerous studies have shown that misunderstandings predominantly result from limited profi ciency in one or more of the languages of the participants in the interethnic encounter, especially the dominant language, including limited awareness of different contextualization cues (e.g., Bremer et al 1996 ;Birkner and Kern 2000 ;Roberts 2000 ;Roberts et al 2005 ). Roberts et al ( 2005 : 473), for instance, found in a study of 232 general practice consultations in four inner -London medical practices that lack of profi ciency in the languages involved in the encounters was the main problem in medical encounters in this multilingual community: " Twenty per cent of all the consultations we fi lmed contained misunderstandings caused by language/cultural differences, where talk itself is the problem.…”
Section: Language In " Intercultural Communication "mentioning
confidence: 99%
“…Ethnic minority groups often have to undertake many aspects of their day-to-day lives with limited English or a mix of English with their first language (Roberts et al, 2005). The provision of high quality language interpretation services is therefore vital for fostering social inclusion and enabling access to public services, including healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication ultimately is positively linked to the achievement of quality health care and positive health outcomes. Past research positively links effective communication with several indicators of quality health care and positive health outcomes such as patients' comprehension of diagnosis and treatment (Lukoschek et al 2003;Roberts et al 2005); patient satisfaction with the healthcare experience (Gallagher et al 2005;Schouten et al 2009); and improved self-care and adherence to treatment (Rivadeneyra et al 2001;Harrington 2004). …”
Section: Discussionmentioning
confidence: 99%